2014
DOI: 10.1111/jphp.12273
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin attenuates transforming growth factor-β1-induced human pulmonary artery smooth muscle cell proliferation and phenotypic switch by inhibiting hypoxia inducible factor-1α and aryl hydrocarbon receptor expression

Abstract: Our study shows that baicalin has the potential to be used as a novel drug in the treatment of pulmonary arterial hypertension pathology by antagonizing HIF-1α and AhR expression and subsequently decreasing HPASMC proliferation and the phenotypic switch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 38 publications
(44 reference statements)
1
35
0
Order By: Relevance
“…Our current finding that the extensive expression of AhR protein in human lung tissues is consistent with our previous reports showing the presence of AhR in pulmonary arterial smooth muscle cells in vitro [11] and in human fetal lung tissues. [22] This broad distribution (endothelium, vascular smooth muscle cells, bronchial epithelium, alveolar sac epithelium, and stromal cells) of AhR in human lung tissues implies the overall importance of AhR in mediating function of different types of human lung cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our current finding that the extensive expression of AhR protein in human lung tissues is consistent with our previous reports showing the presence of AhR in pulmonary arterial smooth muscle cells in vitro [11] and in human fetal lung tissues. [22] This broad distribution (endothelium, vascular smooth muscle cells, bronchial epithelium, alveolar sac epithelium, and stromal cells) of AhR in human lung tissues implies the overall importance of AhR in mediating function of different types of human lung cells.…”
Section: Discussionsupporting
confidence: 93%
“…AhR has been reported to express in human pulmonary artery smooth muscle cells (HPASMCs) in vitro [11] and in human fetal lung tissues, [22] and is associated with Baicalin-inhibited proliferation of HPASMCs. [11] However, it is unknown if the ITE/AhR pathway regulates growth of HPAECs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 To the best of our knowledge, only 1 study has reported a role for AhR in PH, whereby inhibition of TGF-β1 using baicalin led to a decrease in hPASMC proliferation through a decrease in AhR. 19 AhR antagonism is considered a promising mode of treatment and preventive target for diseases, such as gastric and breast cancer and nitric oxidedependent vasculature diseases. 41,42 We found elevated expression of AhR in vehicle SuHx rats, particularly in occluded lesions, and this was reversed by metformin.…”
mentioning
confidence: 99%
“…18 One transcription factor for CYP1B1 is the aryl hydrocarbon receptor (AhR), suppression of which has been shown to be antiproliferative (protective) in PH. 19 Metformin is a well-established drug for use in type 2 diabetes mellitus 20,21 and has been demonstrated to activate AMP-activated protein kinase (AMPK) in many tissues, although AMPK does not underlie the hypoglycemic actions of metformin. 22 AMPK is a ubiquitously expressed serine/threonine protein kinase, which plays a critical role in cellular and organ metabolism.…”
mentioning
confidence: 99%